2012
DOI: 10.1152/jn.01051.2011
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap: global disparity processing in the human visual cortex

Abstract: The human stereoscopic system is remarkable in its ability to utilize widely separated features as references to support fine depth discrimination. In a search for possible neural substrates of this ability, we recorded high-density EEG and used a distributed inverse technique to estimate population-level disparity responses in five regions of interest (ROIs): V1, V3A, hMT+, V4, and lateral occipital complex (LOC). The stimulus was a central modulating disk surrounded by a correlated "reference" annulus presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 53 publications
1
26
0
Order By: Relevance
“…Recent fMRI studies have demonstrated that both areas hMTϩ and V3A are highly responsive to various aspects of MID (Rokers et al 2009). In our previous work, we emphasized that the V3A ROI responded strongly to a central disk alternating between disparities (Cottereau et al 2012b(Cottereau et al , 2012c. Our connectivity analysis extends these results by suggesting that both the hMTϩ and V3A ROIs are con-nected within a cortical network specifically devoted to the processing of MID.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Recent fMRI studies have demonstrated that both areas hMTϩ and V3A are highly responsive to various aspects of MID (Rokers et al 2009). In our previous work, we emphasized that the V3A ROI responded strongly to a central disk alternating between disparities (Cottereau et al 2012b(Cottereau et al , 2012c. Our connectivity analysis extends these results by suggesting that both the hMTϩ and V3A ROIs are con-nected within a cortical network specifically devoted to the processing of MID.…”
Section: Discussionsupporting
confidence: 79%
“…In the MID condition, dots moved out-of-phase between the two eyes and the three bars were perceived as moving in depth between 4 arcmin uncrossed and 4 arcmin crossed. The stimulation frequency was identical to the one used in our previous studies (Cottereau et al 2012b(Cottereau et al , 2012c. At this frequency, our stimuli moved at a speed of 0.28°·s Ϫ1 ·eye Ϫ1 .…”
Section: Methodsmentioning
confidence: 99%
“…EEG artifacts were eliminated off-line using standard procedure whose description can be found in (Cottereau et al 2012c). Before the source imaging procedure (see section 2.8), data were segmented into one-second trials corresponding to one full cycle of the 1Hz disparity display.…”
Section: Methodsmentioning
confidence: 99%
“…R. Soc. B 371: 20150257 depth [29,33,34]). The findings most likely explain why the subjects in some previous studies failed to discriminate disparity in aRDSs [21,35].…”
Section: Reversed Depth In Anti-correlated Random-dot Stereogramsmentioning
confidence: 99%